2021
DOI: 10.1016/j.isprsjprs.2020.10.018
|View full text |Cite
|
Sign up to set email alerts
|

From local to global: A transfer learning-based approach for mapping poplar plantations at national scale using Sentinel-2

Abstract: Reliable estimates of poplar plantations area are not available at the French national scale due to the unsuitability and low update rate of existing forest databases for this short-rotation species. While supervised classification methods have been shown to be highly accurate in mapping forest cover from remotely sensed images, their performance depends to a great extent on the labelled samples used to build the models. In addition to their high acquisition cost, such samples are often scarce and not fully re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 72 publications
(85 reference statements)
2
13
0
Order By: Relevance
“…Active learning improved overall model performance relative to randomized training site selection, in line with findings from two recent efforts (Debats et al, 2017;Hamrouni et al, 2021). Although the relative performance gains that we observed were smaller (e.g., Debats et al, 2017 found 29% higher model performance after one iteration, and 8% higher on the final iterations), those comparisons were made by starting with a training sample that was <1/10 the size of ours.…”
Section: Error Mitigation Featuressupporting
confidence: 90%
See 1 more Smart Citation
“…Active learning improved overall model performance relative to randomized training site selection, in line with findings from two recent efforts (Debats et al, 2017;Hamrouni et al, 2021). Although the relative performance gains that we observed were smaller (e.g., Debats et al, 2017 found 29% higher model performance after one iteration, and 8% higher on the final iterations), those comparisons were made by starting with a training sample that was <1/10 the size of ours.…”
Section: Error Mitigation Featuressupporting
confidence: 90%
“…We couple the labelling platform with a machine learning model inside an active learning (Cohn et al, 1994;Tuia et al, 2011) framework, in which the model is trained interactively, using the model's prediction uncertainty over unlabelled areas to select new sites for additional labelling (Cohn et al, 1994;Tuia et al, 2011). This approach helps boost the performance of the classifier while reducing the overall number of labels required to achieve a given level of performance (Debats et al, 2017;Hamrouni et al, 2021). An unsupervised segmentation step is then applied to convert pixel-wise cropland predictions into vectorized maps of individual field boundaries.…”
Section: Introductionmentioning
confidence: 99%
“…The active learning approach helped to improve overall model performance relative to randomized training site selection, in line with findings from two recent efforts (Debats et al 2017, Hamrouni et al 2021. Although the performance gains relative to randomized model training that we observed were smaller (e.g.…”
Section: Error Mitigation Featuressupporting
confidence: 89%
“…Therefore, the Simpson index (" r 2 = 0.67) is more useful for monitoring and prediction using satellite sensors on a large geographical scale. Heterogeneity indices (i.e., WSLR, growth index and texture diversity) measures also showed an " r 2 > 0.35, which is promising despite the fact that their links to remote sensing signals are not as clear as those for species diversity [9].…”
Section: Large-area Plant Diversity Indices Spatial Distributionmentioning
confidence: 91%
“…Therefore, large-area wall-to-wall maps on plant diversity in forests, as well as spatial changes in its distribution, are frequently required in the forestry operations and conservation of relevant sites [7,8]. Such spatially explicit maps are vital for ecological function stability [5,9,10], exotic species invasion assessments [11], and prevention of plant diseases and insect pests [3,12]-particularly in maintaining the stability of plant community composition [2,6,10,13].…”
Section: Introductionmentioning
confidence: 99%